2023
DOI: 10.1108/jbim-06-2021-0297
|View full text |Cite
|
Sign up to set email alerts
|

Opportunism in an emerging market – franchisee perspective

Abstract: Purpose Although multiple forms of governance mechanisms have been studied to address the opportunistic behavior in franchising, research has not shed light on franchise systems operating in emerging markets despite exponential growth in these markets. To address this gap, this study aims to test the direct effects of different governance mechanisms on franchisee’s opportunism and moderating effects of franchisee’s relationship satisfaction on the relationship between different governance mechanisms and franch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…The synergy of big data collection, analytics, and insights capabilities is crucial for achieving high levels of green process innovation. Academic research on innovation has been largely empirical in recent years, with both the business community and academics showing great interest in the topic ( Luu et al, 2023 ; Panda et al, 2023 ; Sørensen et al, 2023 ; Shah & Saqib, 2023 ; Jell-Ojobor, Alon & Windsperger, 2022 ; Hsu & Jang, 2009 ; Sadovnikova, Kacker & Mishra, 2023 ). Paparoidamis et al (2019) found that the degree of innovation in eco-friendly attributes positively affects consumers’ perception of a product’s eco-friendliness and willingness to adopt it.…”
Section: Related Workmentioning
confidence: 99%
“…The synergy of big data collection, analytics, and insights capabilities is crucial for achieving high levels of green process innovation. Academic research on innovation has been largely empirical in recent years, with both the business community and academics showing great interest in the topic ( Luu et al, 2023 ; Panda et al, 2023 ; Sørensen et al, 2023 ; Shah & Saqib, 2023 ; Jell-Ojobor, Alon & Windsperger, 2022 ; Hsu & Jang, 2009 ; Sadovnikova, Kacker & Mishra, 2023 ). Paparoidamis et al (2019) found that the degree of innovation in eco-friendly attributes positively affects consumers’ perception of a product’s eco-friendliness and willingness to adopt it.…”
Section: Related Workmentioning
confidence: 99%